Avenida Brigadeiro Faria Lima e suas dualidades - Giannoto, Joice Chimati (2019)
The busy Brigadeiro Faria Lima Avenue was not always like this. It had its origin from the calm Iguatemi Street, that was beyond the suburban limits of the city. Throughout its process of transformation, dualities emerged that are noticeable in today's Faria Lima. What was beyond the suburban boundaries of the city is now one of the largest tertiary poles in the city. The street that housed chambers now has office buildings. The buildings with the office configuration gave room for the corporate configuration. The ground floor of the buildings with shops and galleries, so alive in the old Faria Lima, have become more monotonous and now only allow entrance of their condominiums. This thesis investigates the transformations undergone by the Faria Lima Avenue over time and compares not only the old Iguatemi with the current Faria Lima, but also the dynamic between its 'old' stretch and its 'new' stretches.